Assessment framework to predict sensitivity of marine calcifiers to ocean alkalinity enhancement – identification of biological thresholds and importance of precautionary principle - N. Bednaršek; H. van de Mortel; G. Pelletier; G. Pelletier; M. García-Reyes; R. A. Feely; A. G. Dickson; A. G. Dickson (Biogeosciences)
Ocean alkalinity enhancement (OAE), one of the marine carbon dioxide removal strategies, is gaining recognition in its ability to mitigate climate change and ocean acidification (OA). OAE is based on adding alkalinity to open-ocean and coastal marine systems through a variety of different approaches, which raises carbonate chemistry parameters (such as pH, total alkalinity, aragonite saturation state) and enhances the uptake of carbon dioxide (CO2) from the atmosphere. There are large uncertainties in both short- and long-term outcomes related to potential environmental impacts, which would ultimately have an influence on the social license and success of OAE as a climate strategy. This paper represents a synthesis effort, leveraging on the OA studies and published data, observed patterns, and generalizable responses. Our assessment framework was developed to predict the sensitivity of marine calcifiers to OAE by using data originating from OA studies. The synthesis was done using raw experimental OA data based on 68 collected studies, covering 84 unique species and capturing the responses of 11 biological groups (calcifying algae, corals, dinoflagellates, mollusks, gastropods, pteropods, coccolithophores, annelids, crustacean, echinoderms, and foraminifera), using regression analyses to predict biological responses to NaOH or Na2CO3 addition and their respective thresholds. Predicted responses were categorized into six different categories (linear positive and negative, threshold positive and negative, parabolic and neutral) to delineate responses per species. The results show that 34.4 % of responses are predicted to be positive (N=33), 26.0 % negative (N=25), and 39.2 % (N=38) neutral upon alkalinity addition. For the negatively impacted species, biological thresholds, which were based on 50 % reduction of calcification rate, were in the range of 50 to 500 µmol kg−1 NaOH addition. Thus, we emphasize the importance of including much lower additions of alkalinity in experimental trials to realistically evaluate in situ biological responses. However, it is important to note our results do not consider equilibration with the atmosphere and are thus only applicable to short-term and near-field application. The primary goal of the research was to provide an assessment of biological rates and thresholds predicted under NaOH /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="880d1b22cfae9b4167ff115d05c6894c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-473-2025-ie00001.svg" width="8pt" height="14pt" src="bg-22-473-2025-ie00001.png"/></svg:svg> Na2CO3 addition that can serve as a tool for delineating OAE risks. This will help guide and prioritize future OAE biological research and regional monitoring efforts and will also aid in communicating risks to stakeholders. This is important given the fact that at least some of the current OAE approaches do not always assure safe biological space. With 60 % of responses being non-neutral, a precautionary approach for OAE implementation is warranted, identifying the conditions where potential negative ecological outcomes could happen, which is key for scaling up and avoiding ecological risks.